2014
DOI: 10.1038/ncomms4441
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional imaging of cavity vacuum with single atoms localized by a nanohole array

Abstract: Zero-point electromagnetic fields were first introduced to explain the origin of atomic spontaneous emission. Vacuum fluctuations associated with the zero-point energy in cavities are now utilized in quantum devices such as single-photon sources, quantum memories, switches and network nodes. Here we present three-dimensional (3D) imaging of vacuum fluctuations in a high-Q cavity based on the measurement of position-dependent emission of single atoms. Atomic position localization is achieved by using a nanoscal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…This allows us to observe a modulation of the excitedstate lifetime by a factor of 9.8. In contrast to the Purcell effect [21][22][23][24] , where a cavity is used to modify the lifetime, in this work we have a fully open system with a continuous spectrum of modes. The Purcell effect has been extensively studied in recent years owing to its importance in superconducting qubit systems 14,25 .…”
mentioning
confidence: 96%
“…This allows us to observe a modulation of the excitedstate lifetime by a factor of 9.8. In contrast to the Purcell effect [21][22][23][24] , where a cavity is used to modify the lifetime, in this work we have a fully open system with a continuous spectrum of modes. The Purcell effect has been extensively studied in recent years owing to its importance in superconducting qubit systems 14,25 .…”
mentioning
confidence: 96%
“…|1 − g (2) (0)| 1), the third term in Eq. (19) becomes negligibly small compared to the second term. The skewness contained in the last term reflects the degree of asymmetry of the distribution.…”
Section: Photon Correlation In the Cavity-qed Microlasermentioning
confidence: 96%
“…The vacuum is regarded to have a zero-point energy and has certain fluctuations as confirmed from the Casimir effect [13] or their visualization [14]. In the context of vacuum particles, it was experimentally observed that injecting laser light into the vacuum led to the generation of electron-positron pairs (EPPs) [15].…”
Section: Discussionmentioning
confidence: 99%